EFFECTS OF MARKETING MIX, COUNTRY OF ORIGIN IMAGE, ETHNOCENTRISM AND ANIMOSITY ON CHINESE SMARTPHONES’ BRAND IMAGE IN MYANMAR - Zin Hein, Shwe Kyi; Piriyapada, Sunida (Strategic Perspectives on Business and Marketing Management, 2023)
The objectives of this research are to study the effects of marketing mix (4P’s), country of origin image (COO image), ethnocentrism and animosity on Chinese smartphone brand image; and to explore the relationship between brand image and purchase intention of Chinese smartphones in Myanmar. In this research, the convenient sampling method and quantitative data collection method were applied. The targeted respondents are in generation Y millennials who use or intend to buy Chinese smartphones in Magway, Myanmar. Questionnaires were taken with a five-point Likert scale from 400 respondents. As for data analysis methods, reliability test, descriptive statistics, correlation, and linear regression analyses were being selected in this study. The results show that most of the hypotheses are significant level (p <0.05) e.g. product, price, promotion, COO image, and ethnocentrism have positive effects on Chinese smartphone brand image in Myanmar. Moreover, brand image is positively related with purchase intention. This study shows that those significant variables are important for marketers in building strong brand image towards purchase intention in the international market.